The Impact of Game-Based Learning on Student Competencies in Science: A systematic Review - Safitri, Ria Rochmi; Rahmania, Ulya Ghifrani; Putri, Anggraita Febriana; Jumadi, Jumadi (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikdasmen, 2025)
Game-Based Learning is an application that encourages active engagement and enhances knowledge and skills. Its effectiveness in fostering student competencies has been proven and applies in various fields. This systematic review analyzes the science topics, student competencies, and learning outcomes associated with Game-Based Learning implementation in primary and secondary education. The method used refers to the procedures outlined by Kitchenham and Charters. The reporting adheres to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The research sample consisted of 22 articles extracted from 478 articles based on predetermined inclusion and exclusion criteria. The review results show that GBL is applicable across all core science domains-namely physics, biology, and chemistry. The competencies that can be improved using Game-Based Learning consist of three aspects, namely affective, cognitive, and psychomotor. Science learning using Game-Based Learning can significantly improve the three students’ competencies in almost all studies. To conclude, Game-Based Learning can serve as an effective and recommended learning strategy to support the digital transformation of science education.